Microfinance in the margins: understanding women's financial capabilities in South Kivu, Democratic Republic of Congo - Bullock, Renee (International Livestock Research Institute, 2018)
Presented by Renee Bullock (IITA/ILRI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.